2016
DOI: 10.1051/0004-6361/201527983
|View full text |Cite
|
Sign up to set email alerts
|

Metallicity from Type II supernovae from the (i)PTF

Abstract: Type IIP supernovae (SNe IIP) have recently been proposed as metallicity (Z) probes. The spectral models of Dessart et al. (2014, MNRAS, 440, 1856 showed that the pseudo-equivalent width of Fe ii λ5018 (pEW 5018 ) during the plateau phase depends on the primordial Z, but there was a paucity of SNe IIP exhibiting pEW 5018 that were compatible with Z < 0.4 Z . This lack might be due to some physical property of the SN II population or to the fact that those SNe have been discovered in luminous, metal-rich targ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
24
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 24 publications
(38 reference statements)
6
24
1
1
Order By: Relevance
“…Our pEW results clearly support previous findings from Dessart et al (2014); Anderson et al (2016); Taddia et al (2016); Gutiérrez et al (2018). Our SNe are in faint galaxies (absolute M r > −17), which are expected to be of low metallicity.…”
Section: Metallicitysupporting
confidence: 93%
“…Our pEW results clearly support previous findings from Dessart et al (2014); Anderson et al (2016); Taddia et al (2016); Gutiérrez et al (2018). Our SNe are in faint galaxies (absolute M r > −17), which are expected to be of low metallicity.…”
Section: Metallicitysupporting
confidence: 93%
“…Nugent et al (2006) proposed to use the Hβ λ4861 absorption line, which is stronger than the weaker Fe II absorption line but also present in the early spectrum. The original correlation between the Hβ λ4861 and the Fe II velocities found by Nugent et al (2006) was revisited recently by Poznanski et al (2010) and Takáts & Vinkó (2012). Using 28 spectra over 5 of 40 days after the explosion, Poznanski et al (2010) v H .…”
Section: Photospheric Expansion Velocitiesmentioning
confidence: 97%
“…From an observational point of view, Anderson et al (2016) and Taddia et al (2016), using SNeII from the CSP-I and the intermediate Palomar Transient Factory (iPTF), respectively, showed that the equivalent width of the Fe II (EW Fe ) and the absolute magnitude at maximum peak are correlated in the sense that SNeII with smaller EW Fe tend to be brighter.…”
Section: Sensitivity To Progenitor Metallicity?mentioning
confidence: 99%
“…In a sample by Taddia et al (2016), the strength of the Fe II λ5018 feature was used to determine the metallicity according to the method of Dessart et al (2014). In Fig.…”
Section: Spectral Propertiesmentioning
confidence: 99%